The Effect of Six Weeks of High-Intensity Interval Training With Zinc Supplementation on Some Humoral Immunity Markers in Female Futsal Players - Malihe Saeedy; Nahid Bijeh; Mahtab Moazzami (The Society of Aging and Physical Activity (SAPA), 2018)
Background. It seems strenuous trainings have a suppressing effect on the immune function and athletes performing such trainings are probably prone to infectious diseases due to weakened immune system. Objectives. The aim of this study was to examine the effect of six weeks of high-intensity interval training (HIIT) with and without zinc ‎supplementation on serum immunoglobulin concentrations in female futsal players. Mthods. Thirty-two female futsal players were randomly divided into 4 groups like placebo, Zinc, HIIT+Placebo ‎and Zinc+HIIT. All athletes had to attend futsal-specific training 3 sessions per week. Zinc and Placebo groups took ‎30 mg ‎day−1 of zinc gluconate or dextrose, respectively, and HIIT groups performed 6-10 repetitions of a 30-second running at 100% of VO2peak with ‎4-minutes rest between the efforts during six weeks. Results. IgM levels decreased significantly in placebo group (from 136.25±34.44 to 119±33.53, p=0.003) and Zinc group (from 143.25±52.96 to 123.62±50.33, p=0.005). 6 weeks of HIIT did not change the levels of IgA, IgM and IgG significantly (p>0.05). HIIT along with Zinc augmented IgA value (from 179.75±54.49 to 211.12±89.22, p=0.049), significantly; It also increased IgM‎ and IgG levels which were not significant (p>0.05). Conclusion. It can be concluded that 6 weeks of HIIT had no suppressing effect on the immune system in female futsal players; even HIIT along with Zinc supplementation improved the immune system via increasing IgA value.